Using Satellite Images of Environmental Changes to Predict Infectious Disease Outbreaks - Ford, Timothy E.; Rita R. Colwell; Rose, Joan B.; Morse, Stephen S.; Rogers, David J.; Yates, Terry L. (Emerging Infectious DiseasesEmerg Infect DisEmerging Infectious DiseasesEmerg Infect Dis, 2009)
A strong global satellite imaging system is essential for predicting outbreaks., Recent events clearly illustrate a continued vulnerability of large populations to infectious diseases, which is related to our changing human-constructed and natural environments. A single person with multidrug-resistant tuberculosis in 2007 provided a wake-up call to the United States and global public health infrastructure, as the health professionals and the public realized that today’s ease of airline travel can potentially expose hundreds of persons to an untreatable disease associated with an infectious agent. Ease of travel, population increase, population displacement, pollution, agricultural activity, changing socioeconomic structures, and international conflicts worldwide have each contributed to infectious disease events. Today, however, nothing is larger in scale, has more potential for long-term effects, and is more uncertain than the effects of climate change on infectious disease outbreaks, epidemics, and pandemics. We discuss advances in our ability to predict these events and, in particular, the critical role that satellite imaging could play in mounting an effective response.